Direct-current low-power-consumption nanoscale semiconductor electric heat tracing diaphragm
By using nano-organic semiconductor ink spraying and micro-nano groove etching technology in the electric heat-tracing diaphragm, combined with the interwoven design of the composite electrode layer and hollow structure fibers, the problem of uneven heating of the traditional electric heat-tracing diaphragm is solved, and more uniform heating and better thermal insulation performance are achieved.
Patent Information
- Application Number
- CN202510259520.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-06
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2045-03-06
AI Technical Summary
It is difficult to achieve a completely uniform temperature distribution during the heating process of traditional electric heating wires, and the local temperature is prone to problems such as too high or too low.
The DC low-power nano-level semiconductor electrical heat tracing film is used to prepare nano-organic semiconductor ink through inkjet printing technology to form a heating layer, and micro-nano grooves are etched on the surface of the heating layer, and electrode layers are prepared by deposition of titanium, manganese oxide and gold materials. The composite fibers with hollow structures are prepared by using the interwoven method as the thermal insulation buffer layer.
The local resistance uniformity of the heating layer is achieved, hot spots or cold spots are avoided, and the uniformity of heating is improved. Through the interwoven structure of composite fibers, the insulation performance and overall structure stability are enhanced, and the service life is extended.
Smart Images

Figure CN119743858A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electric heating diaphragms, in particular to a direct current low-power nanometer-level semiconductor electric heating diaphragm. Background Art
[0002] In the petroleum, chemical, natural gas and other industries, a large number of pipelines are used to transport various fluids. In cold environments or when transporting fluids that are easy to solidify and have high viscosity (such as crude oil and heavy oil), the pipelines need to be heated. Electric heating diaphragms can fit tightly on the surface of the pipelines, effectively maintain the temperature of the pipelines, and ensure the smooth transportation of the fluids. In buildings, they can be used for floor heating, roof snow melting and de-icing, etc. In floor heating systems, electric heating diaphragms are installed under the floor. By adjusting the current, the floor temperature can be accurately controlled to provide a comfortable heating environment for the room. In terms of roof snow melting and de-icing, electric heating diaphragms can prevent snow and ice from accumulating on the roof, avoiding damage to the building structure caused by ice and snow accumulation, and also reducing the threat to pedestrian safety caused by falling ice and snow. It is difficult to achieve completely uniform distribution of heating materials in traditional electric heating wire heating electric heating diaphragms, which causes the electric heating diaphragm to have local temperatures that are too high or too low during operation. Unreasonable design of the spacing of the heating wires or displacement of the heating wires during installation will lead to uneven heating. For this reason, we propose a DC low-power nano-scale semiconductor electric heating diaphragm. Summary of the invention
[0003] The purpose of the present invention is to provide a direct current low power consumption nanometer-level semiconductor electric heating diaphragm.
[0004] In order to solve the problems raised in the above background technology, the present invention provides the following technical solutions: a DC low-power nano-scale semiconductor electric heating diaphragm, comprising preparing a heating layer, preparing an electrode layer, and adding a heat-insulating buffer layer between the heating layer and the electrode layer to form the electric heating diaphragm. The specific preparation steps of the DC low-power nano-scale semiconductor electric heating diaphragm are as follows: Step 1: Compounding an organic semiconductor material with nano-silver particles to form a nano-organic semiconductor ink, and spraying the nano-organic semiconductor ink onto a substrate surface by an inkjet printer to form a heating layer; Step 2: etching micro-nano grooves on the base surface of the heating layer using a mold having a groove pattern; Step 3: Use titanium, manganese dioxide and gold to sequentially deposit three materials to prepare a layered composite electrode layer, and perform interface treatment between each electronic level layer to enhance the binding force and charge transfer performance between each electronic pole layer; Step 4: using nano-organic semiconductor materials to prepare composite fibers with a hollow structure; Step 5: Using an interweaving method, two fiber bundles with different properties are interwoven to form a heat-insulating buffer layer; Step 6: Assemble the heating layer, electrode layer and thermal insulation buffer layer into an electric heating diaphragm, perform performance tests and quality inspections, and package qualified electric heating diaphragms.
[0005] As a further scheme of the present invention: in the step 1, the nanosilver particles are dispersed in a sodium dodecyl sulfate solution to prepare a nanosilver particle dispersion, the concentration of the sodium dodecyl sulfate is set to 1%-5% of the mass of the nanosilver particles, a 3-hexylthiophene monomer with a purity of 99% is prepared, and the 3-hexylthiophene monomer is dissolved in anhydrous chloroform under nitrogen protection to prepare a 0.1 mol / L-0.5 mol / L solution, and then ferric chloride initiator is added to the solution, and the molar ratio of ferric chloride to 3-hexylthiophene monomer is set to 0.01-0.1, and the solution is stirred at a temperature of 0°C-5°C at a rate of 60r / min-100r / min for 24h-48h to obtain a mixed solution, and then the nanosilver particle dispersion is added to the mixed solution, and an ultrasonic disperser is used to disperse for 30min-60min at a frequency of 30kHz-50kHz to obtain a nano-organic semiconductor ink.
[0006] As a further scheme of the present invention: in the step 1, a polyimide polymer is used as the base material of the electric heating diaphragm, a nano-organic semiconductor ink is loaded into an ink cartridge of an inkjet printer, and a nozzle is used to spray the nano-organic semiconductor ink on the surface of the substrate to form a pattern, the spray frequency of the nozzle is set to 1kHz-10kHz, and the distance between the nozzle and the substrate is set to 0.1mm-1mm. The nano-organic semiconductor ink with a thickness of 100um-500um is sprayed on the surface of the substrate, and the substrate sprayed with the nano-organic semiconductor ink is added to a drying oven for drying, the drying temperature is set to 60℃-100℃, and the drying time is set to 10min-30min to form a heating layer in the electric heating diaphragm.
[0007] As a further solution of the present invention: in the step 2, an electron beam lithography machine is used to draw a wavy micro-nano groove pattern on the surface of the silicon mold, the wavelength of the wave is set to 1um-10um, the amplitude is 100nm-500nm, the width of the groove is set to 50nm-500nm, the depth is set to 100nm-1000nm, the spacing between adjacent grooves is set to 200nm-1000nm, the acceleration voltage of the electron beam lithography machine is set to 5kV-30kV, and the beam current is set to 1nA-10nA , place the silicon mold with the micro-nano groove pattern on the surface of the heating layer material, and put it into the hot embossing equipment, and emboss it at a temperature of 100℃-150℃ and a pressure of 50MPa-100MPa for 5min-10min. After the embossing is completed, use oxygen plasma to transfer the groove pattern to the heating layer material, set the etching power to 50W-200W, the air pressure to 0.5Pa-5Pa, and the etching time to 10min-60min, and etch a wavy micro-nano groove pattern on the surface of the heating layer.
[0008] As a further solution of the present invention: in the step three, titanium is used as the bottom layer in the composite electrode layer, a titanium layer with a thickness of 10nm-100nm is deposited on the substrate by magnetron sputtering technology, hydroxyl groups are introduced on the surface of the titanium layer by chemical adsorption, the substrate with the titanium layer is immersed in a solution containing hydrogen peroxide and sodium hydroxide, and the reaction is carried out at a temperature of 40°C-60°C for 30min-60min to form a hydroxylated surface layer on the surface of the titanium layer, and then the substrate is transferred to a solution containing manganese ions, and manganese ions are adsorbed on the surface of the hydroxylated titanium layer through Ti-O-Mn chemical bonds, and two Manganese oxide is used as the middle layer in the composite electrode layer. Manganese dioxide with a thickness of 100nm-500nm is deposited on the surface of the bottom layer by chemical deposition. The substrate is placed in a plasma treatment device, oxygen is introduced as a reaction gas, the radio frequency power is adjusted between 50W-200W, and the treatment time is 5min-30min. Oxygen plasma generates oxygen free radicals and peroxyl free radicals on the surface of manganese dioxide. Gold is used as the top layer in the composite electrode layer. A gold layer with a thickness of 50nm-200nm is deposited on the middle layer by magnetron sputtering technology to prepare the electrode layer in the electric heating membrane.
[0009] As a further solution of the present invention: in the step 4, 4 、 -diaminodiphenyl ether was dissolved in N-methyl-2-pyrrolidone solution to prepare diamine solution, 4,4 、The concentration of diaminodiphenyl ether is set to 0.1mol / L-0.5mol / L, and then pyromellitic dianhydride is added to the diamine solution, and the molar ratio of diamine to dianhydride is set to 1:1. The mixed solution is added to an electric stirrer and stirred at a temperature of 0℃-5℃ at a rate of 60r / min-100r / min for 4h-8h to obtain a polyamic acid solution. Boron nitride particles with a particle size of 10nm-100nm are selected, and the boron nitride particles are added to the N-methyl-2-pyrrolidone solution, and then the polyethylene is added. The polyvinyl pyrrolidone dispersant is used in an amount of 1%-5% of the mass of the boron nitride nanoparticles. The mixed solution is added into an ultrasonic disperser and dispersed for 30min-60min at a frequency of 20kHz-40kHz to obtain a boron nitride nanoparticle dispersion. The boron nitride nanoparticle dispersion is added into a polyamic acid solution to prepare an outer tube solution. The amount of boron nitride nanoparticles added is 1%-10% of the mass of the polyamic acid. Polyvinyl alcohol is dissolved in water to prepare an inner tube solution with a concentration of 5%-10%.
[0010] As a further solution of the present invention: in the step 4, the inner tube solution is added to the inner tube of the coaxial co-spinning device, the outer tube solution is added to the outer tube of the coaxial co-spinning device, the flow rate of the inner tube solution is set to 0.1mL / h-0.5mL / h, the flow rate of the outer tube solution is set to 0.5mL / h-2mL / h, the spinning voltage is set to 10kV-30kV, the distance between the spinneret and the receiving device is set to 10cm-30cm, the spinning device is turned on to spray the inner tube solution and the outer tube solution from the concentric spinneret at the same time to form a composite fiber with a diameter of 10um-100um, and the composite fiber is The composite fibers are gathered on a receiving device to form a fiber felt, and the collected fiber felt is placed in an oven for thermal imidization treatment, first maintained at a temperature of 100°C-150°C for 1h-2h, then heated to 200°C-300°C at a rate of 2°C / min-5°C / min and maintained for 2h-4h to imidize the polyamic acid and solidify the fiber structure at the same time, and then the solidified fiber is immersed in water at a temperature of 40°C-60°C for 1h-2h to dissolve the polyvinyl alcohol and seep out of the fiber, leaving a hollow pipe structure, to prepare a polyimide fiber with a hollow structure.
[0011] As a further solution of the present invention: in the step 5, the polyimide fiber is made into a fiber bundle with a linear density of 10tex-100tex, and the T700 model carbon fiber is made into a fiber bundle with a linear density of 5tex-80tex, the mass ratio of the polyimide fiber to the carbon fiber is 3:1, and the prepared polyimide fiber bundle and the carbon fiber bundle are respectively placed in two feeding devices of the air interlacing machine, and the air flow pressure of the air interlacing machine is set to 0.1MPa-0.5MPa, and the air flow rate is set to 10m 3 / h-50m 3 / h, the nozzle angle is set to 30°-60°, the feeding speed is set to 10m / min-50m / min, under the action of air flow pressure and flow, the two fiber bundles are blown away and mixed with each other in the interweaving area, and the interwoven fiber fabric is put into the heat setting equipment and treated at a temperature of 180℃-250℃ for 1min-5min to be set to form the thermal insulation buffer layer in the electric heating diaphragm.
[0012] As a further solution of the present invention: in the step six, the heating layer and the electrode layer are added to an ultrasonic cleaning machine, ethanol is selected as an ultrasonic cleaning liquid to remove dust and trace impurities on the surface of the heating layer and the electrode layer, and loose fibers and dust on the surface of the fiber fabric of the thermal insulation buffer layer are removed by compressed air, and a wire is welded to the lead-out end of the electrode layer. After welding, the welding part is encapsulated and protected with insulating glue, and epoxy resin is used to coat the edge of the electric heating diaphragm to form a closed frame with a width of 2mm-10mm, and the heating layer, the electrode layer and the thermal insulation buffer layer are fixed. Together, check the misalignment, wrinkles and bulges between the layers of the assembled electric heating diaphragm, use an insulation resistance tester to detect the resistance value between the electrode layers, the insulation resistance between the electrode layer and the heating layer, and between the electrode layer and the external package, clean the surface of the electric heating diaphragm that has passed the test and place it on anti-static polyethylene foam, put the electric heating diaphragm wrapped with protective material into the aluminum foil composite film, use a heat sealing machine to heat seal the edges of the aluminum foil composite film, set the heat sealing temperature to 120℃-180℃, and the heat sealing width to 5mm-10mm.
[0013] By adopting the above technical solution, compared with the prior art, the beneficial effects of the present invention are: 1. The present invention can effectively adjust the local resistance of the heating layer by uniformly dispersing nanoparticles in the organic semiconductor. Since the nanoparticles are small in size and uniformly distributed, the hot spot or cold spot phenomenon caused by excessive or insufficient local resistance can be avoided. The interaction between the nanoparticles and the organic semiconductor can inhibit heat aggregation. During the heating process, the organic semiconductor may cause material performance degradation or generate local thermal stress due to excessive local heat. When heat concentration occurs locally, the nanoparticles can absorb the excess heat and evenly disperse the heat to the surrounding organic semiconductor materials through heat conduction, thereby avoiding local overheating and ensuring uniform heating. 2. The present invention interweaves hollow polyimide fibers and carbon fibers through an interweaving method to form a complex fiber network structure, which can effectively prevent direct heat transfer and make the heat conduction path between the fibers become tortuous. The high thermal conductivity of carbon fibers can also be utilized in this structure, which can quickly disperse local heat to avoid heat concentration at a certain point. At the same time, it is limited by the thermal insulation effect of the hollow polyimide fibers and cannot be quickly conducted outward, thereby further improving the overall thermal insulation performance of the thermal insulation buffer layer. The interwoven structure enables a synergistic effect between the hollow polyimide fibers and the carbon fibers. The two fibers are entangled and interwoven with each other, making the combination between them tighter and able to effectively transfer stress. This synergistic effect not only improves the tensile strength of the buffer layer, but also enhances its bending strength and fatigue resistance.
[0014] 3. The present invention can significantly increase the contact surface area between the heating layer and the adjacent medium by etching micro-nano grooves on the surface of the heating layer. The micro-nano grooves guide the heat to be conducted along a specific path. When the heating layer generates heat, the heat will preferentially propagate along the direction of the grooves. This directional heat conduction method can reduce the disordered diffusion of heat inside the heating layer, and transfer the heat to the area that needs to be heated more quickly and more concentratedly. The micro-nano grooves disperse the heat generated by the heating layer more evenly. Due to the presence of the grooves, the heat will not accumulate locally on the surface of the heating layer, but will be redistributed on the entire surface of the heating layer through the grooves. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 The figure is a schematic diagram of the preparation process of a DC low-power nano-scale semiconductor electric heating film in an embodiment of the present invention. DETAILED DESCRIPTION
[0016] The specific embodiments of the present invention are further described below in conjunction with the accompanying drawings. It should be noted that the description of these embodiments is used to help understand the present invention, but does not constitute a limitation of the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0017] The present invention discloses a direct current low power consumption nano-scale semiconductor electric heating diaphragm, which comprises preparing a heating layer, preparing an electrode layer, and adding a heat insulating buffer layer between the heating layer and the electrode layer to form the electric heating diaphragm. The specific preparation steps of the direct current low power consumption nano-scale semiconductor electric heating diaphragm are as follows: Step 1: Compounding an organic semiconductor material with nano-silver particles to form a nano-organic semiconductor ink, and spraying the nano-organic semiconductor ink onto a substrate surface by an inkjet printer to form a heating layer; Step 2: etching micro-nano grooves on the base surface of the heating layer using a mold having a groove pattern; Step 3: Use titanium, manganese dioxide and gold to sequentially deposit three materials to prepare a layered composite electrode layer, and perform interface treatment between each electronic level layer to enhance the binding force and charge transfer performance between each electronic pole layer; Step 4: using nano-organic semiconductor materials to prepare composite fibers with a hollow structure; Step 5: Using an interweaving method, two fiber bundles with different properties are interwoven to form a heat-insulating buffer layer; Step 6: Assemble the heating layer, electrode layer and thermal insulation buffer layer into an electric heating diaphragm, perform performance tests and quality inspections, and package qualified electric heating diaphragms.
[0018] In one embodiment of the present invention: in step 1, nanosilver particles are dispersed in a sodium dodecyl sulfate solution to prepare a nanosilver particle dispersion, the concentration of sodium dodecyl sulfate is set to 1%-5% of the mass of the nanosilver particles, 3-hexylthiophene monomer with a purity of 99% is prepared, and the 3-hexylthiophene monomer is dissolved in anhydrous chloroform under nitrogen protection to prepare a 0.1 mol / L-0.5 mol / L solution, and then ferric chloride initiator is added to the solution, and the molar ratio of ferric chloride to 3-hexylthiophene monomer is set to 0.01-0.1, and the mixture is stirred at a temperature of 0°C-5°C at a rate of 60r / min-100r / min for 24h-48h to obtain a mixed solution, and then the nanosilver particle dispersion is added to the mixed solution, and an ultrasonic disperser is used to disperse the mixture at a frequency of 30kHz-50kHz for 30min-60min to obtain a nano-organic semiconductor ink.
[0019] In one embodiment of the present invention: in step one, a polyimide polymer is used as the base material of the electric heating diaphragm, a nano-organic semiconductor ink is loaded into an ink cartridge of an inkjet printer, and a nozzle is used to spray the nano-organic semiconductor ink on the surface of the substrate to form a pattern, the spray frequency of the nozzle is set to 1kHz-10kHz, and the distance between the nozzle and the substrate is set to 0.1mm-1mm. The nano-organic semiconductor ink with a thickness of 100um-500um is sprayed on the surface of the substrate, and the substrate sprayed with the nano-organic semiconductor ink is added to a drying oven for drying, the drying temperature is set to 60℃-100℃, and the drying time is set to 10min-30min to form a heating layer in the electric heating diaphragm.
[0020] In one embodiment of the present invention: in step 2, an electron beam lithography machine is used to draw a wavy micro-nano groove pattern on the surface of the silicon mold, the wavelength of the wave is set to 1um-10um, the amplitude is 100nm-500nm, the width of the groove is set to 50nm-500nm, the depth is set to 100nm-1000nm, the spacing between adjacent grooves is set to 200nm-1000nm, the acceleration voltage of the electron beam lithography machine is set to 5kV-30kV, and the beam current is set to 1nA-10nA. Place the silicon mold with the micro-nano groove pattern on the surface of the heating layer material and put it into the hot embossing equipment. Imprint it at a temperature of 100℃-150℃ and a pressure of 50MPa-100MPa for 5min-10min. After the imprinting is completed, use oxygen plasma to transfer the groove pattern to the heating layer material. The etching power is set to 50W-200W, the air pressure is set to 0.5Pa-5Pa, and the etching time is 10min-60min. Etch a wavy micro-nano groove pattern on the surface of the heating layer.
[0021] In one embodiment of the present invention: in step three, titanium is used as the bottom layer in the composite electrode layer, a titanium layer with a thickness of 10nm-100nm is deposited on the substrate by magnetron sputtering technology, hydroxyl groups are introduced on the surface of the titanium layer by chemical adsorption, the substrate with the titanium layer is immersed in a solution containing hydrogen peroxide and sodium hydroxide, and the reaction is carried out at a temperature of 40°C-60°C for 30min-60min to form a hydroxylated surface layer on the surface of the titanium layer, and then the substrate is transferred to a solution containing manganese ions, and manganese ions are adsorbed on the surface of the hydroxylated titanium layer through Ti-O-Mn chemical bonds, and two Manganese oxide is used as the middle layer in the composite electrode layer. Manganese dioxide with a thickness of 100nm-500nm is deposited on the surface of the bottom layer by chemical deposition. The substrate is placed in a plasma treatment device, oxygen is introduced as a reaction gas, the radio frequency power is adjusted between 50W-200W, and the treatment time is 5min-30min. Oxygen plasma generates oxygen free radicals and peroxyl free radicals on the surface of manganese dioxide. Gold is used as the top layer in the composite electrode layer. A gold layer with a thickness of 50nm-200nm is deposited on the middle layer by magnetron sputtering technology to prepare the electrode layer in the electric heating membrane.
[0022] In one embodiment of the present invention: in step 4, 4,4 、 -diaminodiphenyl ether was dissolved in N-methyl-2-pyrrolidone solution to prepare diamine solution, 4,4 、The concentration of diaminodiphenyl ether is set to 0.1mol / L-0.5mol / L, and then pyromellitic dianhydride is added to the diamine solution, and the molar ratio of diamine to dianhydride is set to 1:1. The mixed solution is added to an electric stirrer and stirred at a temperature of 0℃-5℃ at a rate of 60r / min-100r / min for 4h-8h to obtain a polyamic acid solution. Boron nitride particles with a particle size of 10nm-100nm are selected, and the boron nitride particles are added to the N-methyl-2-pyrrolidone solution, and then the polyethylene is added. The polyvinyl pyrrolidone dispersant is used in an amount of 1%-5% of the mass of the boron nitride nanoparticles. The mixed solution is added into an ultrasonic disperser and dispersed for 30min-60min at a frequency of 20kHz-40kHz to obtain a boron nitride nanoparticle dispersion. The boron nitride nanoparticle dispersion is added into a polyamic acid solution to prepare an outer tube solution. The amount of boron nitride nanoparticles added is 1%-10% of the mass of the polyamic acid. Polyvinyl alcohol is dissolved in water to prepare an inner tube solution with a concentration of 5%-10%.
[0023] In one embodiment of the present invention: in step 4, the inner tube solution is added to the inner tube of the coaxial co-spinning device, the outer tube solution is added to the outer tube of the coaxial co-spinning device, the flow rate of the inner tube solution is set to 0.1mL / h-0.5mL / h, the flow rate of the outer tube solution is set to 0.5mL / h-2mL / h, the spinning voltage is set to 10kV-30kV, the distance between the spinneret and the receiving device is set to 10cm-30cm, the spinning device is turned on to spray the inner tube solution and the outer tube solution from the concentric spinneret at the same time to form a composite fiber with a diameter of 10um-100um, and the composite The fibers are gathered on the receiving device to form a fiber felt, and the collected fiber felt is put into an oven for thermal imidization treatment. First, it is kept at a temperature of 100℃-150℃ for 1h-2h, and then the temperature is increased to 200℃-300℃ at a rate of 2℃ / min-5℃ / min and kept for 2h-4h to imidize the polyamic acid and solidify the fiber structure at the same time. The solidified fiber is then immersed in water at a temperature of 40℃-60℃ for 1h-2h to dissolve the polyvinyl alcohol and seep out of the fiber, leaving a hollow pipe structure, to prepare a polyimide fiber with a hollow structure.
[0024] In one embodiment of the present invention: in step 5, the polyimide fiber is made into a fiber bundle with a linear density of 10tex-100tex, and the T700 model carbon fiber is made into a fiber bundle with a linear density of 5tex-80tex, the mass ratio of the polyimide fiber to the carbon fiber is 3:1, and the prepared polyimide fiber bundle and the carbon fiber bundle are respectively placed in two feeding devices of the air interlacing machine, and the air flow pressure of the air interlacing machine is set to 0.1MPa-0.5MPa, and the air flow rate is set to 10m 3 / h-50m 3 / h, the nozzle angle is set to 30°-60°, the feeding speed is set to 10m / min-50m / min, under the action of air flow pressure and flow, the two fiber bundles are blown away and mixed with each other in the interweaving area, and the interwoven fiber fabric is put into the heat setting equipment and treated at a temperature of 180℃-250℃ for 1min-5min to be set to form the thermal insulation buffer layer in the electric heating diaphragm.
[0025] In one embodiment of the present invention: in step six, the heating layer and the electrode layer are added to an ultrasonic cleaning machine, ethanol is selected as an ultrasonic cleaning liquid, dust and trace impurities on the surface of the heating layer and the electrode layer are removed, loose fibers and dust on the surface of the fiber fabric of the thermal insulation buffer layer are removed by compressed air, a wire is welded at the lead-out end of the electrode layer, and the welding part is encapsulated and protected with insulating glue after welding, epoxy resin is coated along the edge of the electric heating diaphragm to form a closed frame with a width of 2mm-10mm, the heating layer, the electrode layer and the thermal insulation buffer layer are fixed together, the dislocation, wrinkles and protrusions between the layers of the assembled electric heating diaphragm are checked, an insulation resistance tester is used to detect the resistance value between the electrode layers, the insulation resistance between the electrode layer and the heating layer, and between the electrode layer and the external package, the surface of the electric heating diaphragm that has passed the test is cleaned and placed on antistatic polyethylene foam, the electric heating diaphragm wrapped with protective material is placed in an aluminum foil composite film, and the edge of the aluminum foil composite film is heat-sealed using a heat sealing machine, the heat sealing temperature is set to 120℃-180℃, and the heat sealing width is set to 5mm-10mm.
[0026] Embodiment 1: Interface treatment is performed between the titanium layer and the manganese dioxide intermediate layer. Manganese ions are adsorbed on the surface of the hydroxylated titanium layer through the Ti-O-Mn chemical bond, providing better binding sites for the subsequent deposition of manganese dioxide, thereby improving the adhesion and charge transfer performance of the interface. Interface treatment is performed between the manganese dioxide intermediate layer and the gold layer, such as oxygen free radicals (·O) and peroxy free radicals (·O2 - ), these active species can form stronger chemical bonds with the gold layer during the deposition process, improve the bonding strength of the interface and the electron transmission performance. Through interface treatment, the contact resistance between the two adjacent layers of materials is reduced, so that the charge can be transmitted more smoothly between the layers. The energy level structure of the transition layer material can better match the energy level of the two adjacent layers of materials, which is conducive to the transition and transmission of electrons. In the process of electric heating, good charge transmission performance can ensure that the current is evenly distributed in the electrode layer, reduce local overheating, and improve heating efficiency. Interface treatment measures improve the adhesion between the layers and prevent stratification during use. After chemical adsorption or plasma treatment, the bonding force between the two adjacent layers is improved. This enhanced adhesion can ensure that the electrode layer maintains structural integrity under complex working conditions such as long-term thermal cycles and mechanical vibrations, thereby extending the service life of the electric heating membrane.
[0027] Embodiment 2: Make a metal frame that matches the size of the heating layer, place the heating layer in the frame, fix the heating layer in a predetermined position, evenly apply a layer of conductive glue with a thickness of 50um on the bonding surface of the electrode layer, and then accurately place the electrode layer at the corresponding position of the heating layer, use a rubber roller to gently roll it to remove bubbles between the bonding surfaces, ensure that the electrode layer and the heating layer are tightly fitted, and make the conductive glue evenly distributed, then place the thermal insulation buffer layer between the heating layer and the electrode layer, and use a hot pressing method to laminate the thermal insulation buffer layer, the heating layer and the electrode layer at a temperature of 150°C and a pressure of 2MPa, so that the fibers are interwoven and tightly combined with adjacent layers, thereby improving the thermal insulation effect and the stability of the overall structure, and welding wires at the lead-out end of the electrode layer. After welding, use insulating glue to encapsulate and protect the welding parts, and use epoxy resin to coat a closed frame with a width of 5mm along the edge of the electric heating diaphragm.
[0028] Embodiment 3: Use electron beam lithography machine to draw wavy micro-nano groove pattern on the surface of silicon mold, the wavelength of wave is set to 5um, the amplitude is 300nm, the width of groove is set to 200nm, the depth is set to 5000nm, the spacing between adjacent grooves is set to 5000nm, the acceleration voltage of electron beam lithography machine is set to 20kV, the beam current is set to 50nA, place the silicon mold with micro-nano groove pattern on the surface of heating layer material, and put it into hot stamping equipment, and stamp it at 120℃ and 80MPa pressure for 80min. After stamping, use oxygen plasma to transfer groove pattern to heating layer material, the etching power is set to 100W, the air pressure is set to 3Pa, the etching time is 40min, and wavy micro-nano groove pattern is etched on the surface of heating layer. Micro-nano groove can enhance the mechanical interlocking between heating layer and adjacent materials. The presence of groove can also increase the chemical interaction between heating layer and adjacent materials. Because groove increases contact area, there are more opportunities for chemical reaction or physical adsorption between heating layer and adjacent materials.
[0029] As attached Figure 1 As shown, organic semiconductor and nanoparticle composite materials are used, and hollow polyimide fibers and carbon fibers are made into a composite thermal insulation buffer layer by an interweaving method, which can combine the properties of different materials to produce a synergistic effect and increase the service life of the electric heating diaphragm.
[0030] The embodiments of the present invention are described in detail above with reference to the accompanying drawings, but the present invention is not limited to the described embodiments. For those skilled in the art, various changes, modifications, substitutions and variations of these embodiments are made without departing from the principles and spirit of the present invention, and still fall within the scope of protection of the present invention.
[0031] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0032] The above contents are merely examples and explanations of the present invention. Various modifications or additions to the specific embodiments described or replacements in similar ways by technicians in the technical field shall fall within the protection scope of the present invention as long as they do not deviate from the invention or exceed the scope defined by the claims.
[0033] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A direct current low power consumption nano-scale semiconductor electric heating diaphragm, comprising preparing a heating layer, preparing an electrode layer, and adding a heat insulating buffer layer between the heating layer and the electrode layer to form the electric heating diaphragm, characterized in that: The specific preparation steps of the DC low-power nano-scale semiconductor electric heating diaphragm are as follows: Step 1: Compounding an organic semiconductor material with nano-silver particles to form a nano-organic semiconductor ink, and spraying the nano-organic semiconductor ink onto a substrate surface by an inkjet printer to form a heating layer; Step 2: etching micro-nano grooves on the base surface of the heating layer using a mold having a groove pattern; Step 3: Use titanium, manganese dioxide and gold to sequentially deposit three materials to prepare a layered composite electrode layer, and perform interface treatment between each electronic level layer to enhance the binding force and charge transfer performance between each electronic pole layer; Step 4: using nano-organic semiconductor materials to prepare composite fibers with a hollow structure; Step 5: Using an interweaving method, two fiber bundles with different properties are interwoven to form a heat-insulating buffer layer; Step 6: Assemble the heating layer, electrode layer and thermal insulation buffer layer into an electric heating diaphragm, perform performance tests and quality inspections, and package qualified electric heating diaphragms.
2. A DC low-power nano-scale semiconductor electric heating diaphragm according to claim 1, characterized in that: In the step 1, nanosilver particles are dispersed in a sodium dodecyl sulfate solution to prepare a nanosilver particle dispersion, wherein the concentration of the sodium dodecyl sulfate is set to 1%-5% of the mass of the nanosilver particles, a 3-hexylthiophene monomer with a purity of 99% is prepared, and the 3-hexylthiophene monomer is dissolved in anhydrous chloroform under nitrogen protection to prepare a 0.1 mol / L-0.5 mol / L solution, and then a ferric chloride initiator is added to the solution, wherein the molar ratio of ferric chloride to 3-hexylthiophene monomer is set to 0.01-0.1, and the solution is stirred at a temperature of 0° C.-5° C. at a rate of 60 r / min-100 r / min for 24 h-48 h to obtain a mixed solution, and then the nanosilver particle dispersion is added to the mixed solution, and an ultrasonic disperser is used to disperse the solution at a frequency of 30 kHz-50 kHz for 30 min-60 min to obtain a nano-organic semiconductor ink.
3. A DC low power consumption nano-scale semiconductor electric heating film according to claim 2, characterized in that: In the step 1, a polyimide polymer is used as a base material of the electric heating diaphragm, a nano-organic semiconductor ink is loaded into an ink cartridge of an inkjet printer, and a nozzle is used to spray the nano-organic semiconductor ink on the surface of the substrate to form a pattern. The spray frequency of the nozzle is set to 1kHz-10kHz, and the distance between the nozzle and the substrate is set to 0.1mm-1mm. The nano-organic semiconductor ink with a thickness of 100um-500um is sprayed on the surface of the substrate, and the substrate sprayed with the nano-organic semiconductor ink is added to a drying oven for drying. The drying temperature is set to 60°C-100°C, and the drying time is set to 10min-30min to form a heating layer in the electric heating diaphragm.
4. A DC low-power nano-scale semiconductor electric heating diaphragm according to claim 3, characterized in that: In the step 2, an electron beam lithography machine is used to draw a wavy micro-nano groove pattern on the surface of the silicon mold, the wavelength of the wave is set to 1um-10um, the amplitude is 100nm-500nm, the width of the groove is set to 50nm-500nm, the depth is set to 100nm-1000nm, the spacing between adjacent grooves is set to 200nm-1000nm, the acceleration voltage of the electron beam lithography machine is set to 5kV-30kV, the beam current is set to 1nA-10nA, and the silicon mold with the micro-nano groove pattern is placed on the surface of the heating layer material and placed in a hot stamping device. It is imprinted at a temperature of 100℃-150℃ and a pressure of 50MPa-100MPa for 5min-10min. After the imprinting is completed, the groove pattern is transferred to the heating layer material using oxygen plasma, the etching power is set to 50W-200W, the air pressure is set to 0.5Pa-5Pa, and the etching time is 10min-60min to etch a wavy micro-nano groove pattern on the surface of the heating layer.
5. The DC low-power nano-scale semiconductor electric heating film according to claim 2, characterized in that: In the step three, titanium is used as the bottom layer in the composite electrode layer, a titanium layer with a thickness of 10nm-100nm is deposited on the substrate by magnetron sputtering technology, hydroxyl groups are introduced on the surface of the titanium layer by chemical adsorption, the substrate with the titanium layer is immersed in a solution containing hydrogen peroxide and sodium hydroxide, and the reaction is carried out at a temperature of 40°C-60°C for 30min-60min to form a hydroxylated surface layer on the surface of the titanium layer, and then the substrate is transferred to a solution containing manganese ions, and manganese ions are adsorbed on the surface of the hydroxylated titanium layer through Ti-O-Mn chemical bonds, and manganese dioxide is used as the composite electrode layer. The middle layer in the composite electrode layer is prepared by chemical deposition on the surface of the bottom layer to deposit manganese dioxide with a thickness of 100nm-500nm. The substrate is placed in a plasma treatment device, oxygen is introduced as a reaction gas, the radio frequency power is adjusted between 50W-200W, and the treatment time is 5min-30min. The oxygen plasma generates oxygen free radicals and peroxy free radicals on the surface of manganese dioxide. Gold is used as the top layer in the composite electrode layer, and a gold layer with a thickness of 50nm-200nm is deposited on the middle layer by magnetron sputtering technology to prepare the electrode layer in the electric heating membrane.
6. The DC low-power nanoscale semiconductor electric heating film according to claim 1, characterized in that: In step 4, 4,4 、 -diaminodiphenyl ether was dissolved in N-methyl-2-pyrrolidone solution to prepare diamine solution, 4,4 、 The concentration of diaminodiphenyl ether is set to 0.1mol / L-0.5mol / L, and then pyromellitic dianhydride is added to the diamine solution, and the molar ratio of diamine to dianhydride is set to 1:
1. The mixed solution is added to an electric stirrer and stirred at a temperature of 0℃-5℃ at a rate of 60r / min-100r / min for 4h-8h to obtain a polyamic acid solution. Boron nitride particles with a particle size of 10nm-100nm are selected, and the boron nitride particles are added to the N-methyl-2-pyrrolidone solution, and then the polyethylene is added. The polyvinyl pyrrolidone dispersant is used in an amount of 1%-5% of the mass of the boron nitride nanoparticles. The mixed solution is added into an ultrasonic disperser and dispersed for 30min-60min at a frequency of 20kHz-40kHz to obtain a boron nitride nanoparticle dispersion. The boron nitride nanoparticle dispersion is added into a polyamic acid solution to prepare an outer tube solution. The amount of boron nitride nanoparticles added is 1%-10% of the mass of the polyamic acid. Polyvinyl alcohol is dissolved in water to prepare an inner tube solution with a concentration of 5%-10%.
7. A DC low-power nano-scale semiconductor electric heating diaphragm according to claim 6, characterized in that: In the step 4, the inner tube solution is added to the inner tube of the coaxial co-spinning device, and the outer tube solution is added to the outer tube of the coaxial co-spinning device, the flow rate of the inner tube solution is set to 0.1mL / h-0.5mL / h, the flow rate of the outer tube solution is set to 0.5mL / h-2mL / h, the spinning voltage is set to 10kV-30kV, the distance between the spinneret and the receiving device is set to 10cm-30cm, the spinning device is turned on to spray the inner tube solution and the outer tube solution from the concentric spinneret at the same time to form a composite fiber with a diameter of 10um-100um, and the composite fiber is received The fibers are gathered on the device to form fiber felt, and the collected fiber felt is put into an oven for thermal imidization treatment. First, it is kept at a temperature of 100°C-150°C for 1h-2h, and then the temperature is increased to 200°C-300°C at a rate of 2°C / min-5°C / min and kept for 2h-4h to imidize the polyamic acid and solidify the fiber structure at the same time. The solidified fiber is then immersed in water at a temperature of 40°C-60°C for 1h-2h to dissolve the polyvinyl alcohol and seep out of the fiber, leaving a hollow pipe structure, to prepare a polyimide fiber with a hollow structure.
8. The DC low-power nano-scale semiconductor electric heating film according to claim 7, characterized in that: In the step 5, the polyimide fiber is made into a fiber bundle with a linear density of 10tex-100tex, and the T700 model carbon fiber is made into a fiber bundle with a linear density of 5tex-80tex, the mass ratio of polyimide fiber to carbon fiber is 3:1, and the prepared polyimide fiber bundle and carbon fiber bundle are respectively placed in two feeding devices of the air interlacing machine, and the air flow pressure of the air interlacing machine is set to 0.1MPa-0.5MPa, and the air flow rate is set to 10m 3 / h-50m 3 / h, the nozzle angle is set to 30°-60°, the feeding speed is set to 10m / min-50m / min, under the action of air flow pressure and flow, the two fiber bundles are blown away and mixed with each other in the interweaving area, and the interwoven fiber fabric is put into the heat setting equipment and treated at a temperature of 180℃-250℃ for 1min-5min to be set to form the thermal insulation buffer layer in the electric heating diaphragm.
9. A DC low power consumption nano-scale semiconductor electric heating film according to claim 8, characterized in that: In the step six, the heating layer and the electrode layer are added to an ultrasonic cleaning machine, ethanol is selected as an ultrasonic cleaning liquid, dust and trace impurities on the surfaces of the heating layer and the electrode layer are removed, loose fibers and dust on the surface of the fiber fabric of the thermal insulation buffer layer are removed by compressed air, a wire is welded at the lead-out end of the electrode layer, and the welding part is encapsulated and protected with insulating glue after welding, epoxy resin is coated along the edge of the electric heating diaphragm to form a closed frame with a width of 2mm-10mm, the heating layer, the electrode layer and the thermal insulation buffer layer are fixed together, the dislocation, wrinkles and protrusions between the layers of the assembled electric heating diaphragm are checked, an insulation resistance tester is used to detect the resistance value between the electrode layers, the insulation resistance between the electrode layer and the heating layer, and between the electrode layer and the external package, the surface of the electric heating diaphragm that has passed the test is cleaned and placed on antistatic polyethylene foam, the electric heating diaphragm wrapped with protective material is placed in an aluminum foil composite film, and the edges of the aluminum foil composite film are heat-sealed using a heat sealing machine, the heat sealing temperature is set to 120°C-180°C, and the heat sealing width is set to 5mm-10mm.
Citation Information
Patent Citations
Woven flexible planar heating element comprising protective film, and method for producing same
CN111034353A
Flexible electric heating film heating layer and preparation method thereof
CN112566290A
Heater and smoking set comprising same
CN113080521A
Heating body and preparation method thereof, atomization assembly and electronic atomization device
CN117084461A
Power-limited electric tracing band welding-free production process
CN119485824A